Bleeding due to a probable interaction between warfarin and Gouqizi (Lycium Barbarum L.). (2015) - Zhang, Jinhua; Tian, Lihong; Xie, Bixiang
Abstract: Unlike what is widely anticipated by the public, herbal medicines are not always safe despite being natural. We describe a 65-year-old Chinese man taking a prolonged maintenance dose of warfarin who experienced an elevated international normalized ratio (INR) with associated bleeding after drinking Gouqizi (goji berry) wine. This report illustrates that large doses (more than 6–12 g) of Gouqizi can significantly enhance the anticoagulant action of warfarin and may cause similar adverse effects in keeping with three previous reports. Therefore, the use of herbal medicines must adhere to pharmacopoeia-recommended guidelines, including dosage regimes. Doctors should advise patients regarding possible interactions between herbs and warfarin when prescribing and should increase the frequency of INR monitoring for those patients concurrently receiving warfarin and medicinal herbs. Further study is needed to do for the mechanism of interaction between Gouqizi and warfarin.